BRAND IDENTITY: INTRODUCING RENEWED CONCEPT FOR COFFEE SHOPS - Rashid, Sabrina Mohd; Ghose, Kamal; Cohen, David A. (PEOPLE: International Journal of Social Sciences, 2015)
Building a strong brand identity has become a major marketing concern for many services. In previous years, the focus was on the interaction between the organization and the customers. This study extended previous research by focusing on the concept of coffee shops. A qualitative approach with semi-structured interviews was used to explore the food and beverage industry. The interviews were carried out with 15 independent coffee shops in Christchurch, New Zealand. There were two key findings from this research that indicated attentiveness among the respondents about brand identity, first, a distinctive concept and second, having a fresh concept that will assist the process of brand identity creation. This study contributed to our understanding of how brand identity was built and then connected it to the internal culture of the coffee shop. The findings suggested that the process of creating and building a brand identity was more complicated than just creating the visual imagery in order to build distinctiveness.